2022
DOI: 10.1002/ange.202214265
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Non‐Equilibrium Self‐Assembly and Molecular Movements Powered by Electrical Energy**

Abstract: The ability to exploit energy autonomously is one of the hallmarks of life. Mastering such processes in artificial nanosystems can open technological opportunities. In the last decades, light-and chemically driven autonomous systems have been developed in relation to conformational motion and self-assembly, mostly in relation to molecular motors. In contrast, despite electrical energy being an attractive energy source to power nanosystems, its autonomous harnessing has received little attention. Herein we cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…It is important to note electric field based molecular motor and achieving high energy state in a molecular system mainly having mechanical bond based supramolecular assembly system has been reported in recent literature. [34][35][36][37][38][39] In fact, one of the recent study indicated the entropy stored in that type of system. 37 However, none of the cases, effect of further complexity by application of external electric field in transient self-assembly process as discussed here, has been reported.…”
mentioning
confidence: 99%
“…It is important to note electric field based molecular motor and achieving high energy state in a molecular system mainly having mechanical bond based supramolecular assembly system has been reported in recent literature. [34][35][36][37][38][39] In fact, one of the recent study indicated the entropy stored in that type of system. 37 However, none of the cases, effect of further complexity by application of external electric field in transient self-assembly process as discussed here, has been reported.…”
mentioning
confidence: 99%